Formação inicial de professores: o percurso de alunos de estágio supervisionado em Física da UEM, envolvendo a proposta da prática reflexiva, o lúdico e o uso de tecnologias - Pereira, Ricardo Francisco (2013)
This research analyzes the route of the undergraduate physics coursing discipline Supervised Training II in Physics, Universidade Estadual de Maringá, in the second half of the year 2012. It was proposed activities involving reflective practice, and the playful use of technologies for the formation of a teacher whose profile is dynamic, interactive, participatory, reflective and playful. The research is characterized as qualitative research because it seeks to answer particular questions of reality investigated and structured based on action research, concerned with the diagnosis of the problem in a particular context. Using the classification of Franco (2005), is research fits like action research proposal because the strategic transformation of reality has been investigated previously planned without the participation of the subjects. The data were collected through a questionnaire investigative profile of student teachers and a personal memorial delivered at the end of the course. At the memorial each participant reflected on the activities proposed by this research as one of the reviews. The methodology used in the analysis of the memorials was the phenomenological method, whose principle is to achieve the essence of the reflections of those surveyed. The analyzes and reflections of the results showed that the licensees have evolved in the direction of the teacher profile form we want. There was a gradual evolution of undergraduates and a maturing of a future teacher of Physics to take a more participatory, reflective and interactive during activities. Contact and had learned to use various resources and teaching methodologies in order to understand that the initial training is not the final stage of the formation of a teacher, but only the beginning and that you need a continuous search for improvement professional. The activities proposed in this study achieved results that show a significant contribution as a teaching resource in the formation of a reflective teacher, dynamic and interactive. Then we can say that our proposal is feasible and that it is possible to promote an initial training principles best suited to the qualities required today for physics teachers.